Risk Factors for the Occurrence of Benign Paroxysmal Positional Vertigo: A Systematic Review and Meta-Analysis - Chen, Jinbao; Zhao, Weisong; Yue, Xuejing; Zhang, Ping (Frontiers in Neurology, 2020)
The lifetime prevalence of BPPV is high, especially in the elderly.And Benign Paroxysmal Positional Vertigo (BPPV) may increase the risk of ischemic stroke, dementia and fractures, severely reducing quality of life of patients. Many studies have analyzed risk factors for the occurrence of BPPV. But the results of these studies are not identical. We performed this meta-analysis to determine potential risk factors associated with the occurrence of BPPV.Methods: PubMed, Embase, and the Cochrane Library (January 2000 through March 2020) were systematically searched for eligible studies analyzing risk factors for the occurrence of BPPV. Reference lists of eligible studies were also reviewed. We selected observational studies in English with a control group and sufficient data. Pooled odds ratios (ORs) or the mean differences (MDs) and 95% confidence intervals (CIs) were calculated to measure the impacts of all potential risk factors. Heterogeneity among studies was evaluated using the Q test and I 2 statistics. We used the random-effect model or the fixed-effect model according to the heterogeneity among the included studies.